Cell-instructive high-resolution micropatterned polylactic acid surfaces. (24th July 2017) - Barata, David; Dias, Paulo; Wieringa, Paul; van Blitterswijk, Clemens; Habibovic, Pamela
Abstract: Micro and nanoscale topographical structuring of biomaterial surfaces has been a valuable tool for influencing cell behavior, including cell attachment, proliferation and differentiation. However, most fabrication techniques for surface patterning of implantable biomaterials suffer from a limited resolution, not allowing controlled generation of sub-cellular three-dimensional features. Here, a direct laser lithography technique based on two-photon absorption was used to construct several patterns varying in size between 500 nm and 15 μ m. Through replication via an intermediate mold, the patterns were transferred into polylactic acid (PLA), a widely used biomedical polymer, while retaining the original geometry. An osteoblast-like cell line, MG-63 was used for characterizing the morphological response to the topographical patterns. The results indicated that semi-continuous (dashed) lines, with a height of 1 μ m were able to induce cell elongation in the direction of the lines. However, when dashes with a height of 0.5 μ m were combined with perpendicularly crossing continuous lines (rails) with a height of 8 μ m, the contact guidance effect of the dashes was lost and elongation of the cells was observed in the direction of the larger features. A second pattern, consisting of different arrays of pillars showed that, depending on the pillar height, the cells were either able to spread over the pattern or were confined between the pattern features. These differences in the ability of cells to spread further resulted in the formation of tension forces through stress fibers and displacement of vimentin. The method for high-resolution micropatterning of PLA as presented here can also be applied to other biomedical polymers, making it useful both for fundamental studies and for designing new biomaterials with improved functionality.